Vascular structure and function in the medial collateral ligament of anterior cruciate ligament transected rabbit knees. Issue 9 (7th June 2014) - Miller, Daniel; DeSutter, Christopher; Scott, Alex; Koglin, Laurent; Hart, David A.; Salo, Paul; Leonard, Catherine; Mammoto, Takeo; Bray, Robert C.
ABSTRACT To determine if decreased vascular responsiveness in the medial collateral ligament (MCL) of anterior cruciate ligament transected (ACL‐t) rabbit knees is due to pericyte deficiency associated with angiogenesis. Vascular responses to potassium chloride (KCl), phenylephrine, acetylcholine, and sodium nitroprusside (SNP) were evaluated in ACL‐t rabbit knees (n = 6) and control knees (n = 5) using laser speckle perfusion imaging. Ligament degeneration was determined by ultrasound imaging. Vascular and pericyte volume were measured using quantitative immunohistochemical volumetric analysis using CD31 and α‐smooth muscle actin antibodies with co‐localization analysis. Perfusion was increased in the ACL‐t rabbits 2.5‐fold. Responsiveness to phenylephrine, SNP, and acetylcholine was significantly decreased in the ACL knee while no change in KCl responses was seen. MCL ultrasound imaging revealed decreased collagen organization, increased ligament thickness, and increased water content in the ACL‐t MCL. Vascular Volume was increased fourfold in ACL deficient knees, while pericyte volume to endothelial volume was not changed. No difference in CD31 and α‐SMA co‐localization was found. Blood vessels in the MCL of ACL‐t knees do not lack smooth muscle. The MCL vasculature can undergo constrictive response to KCl, but have impaired receptor mediated responses and impaired nitric oxide signaling. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1104–1110, 2014.